Social and Social Security Profile: Influence on the Quality of Life of Patients Undergoing Radiotherapy - Rodrigues , Stella Grigolette (2022)
Introduction: Cancer is being diagnosed more and more frequently all over the world, and advances in radiotherapy treatment are extending the survival time for affected patients, however, little attention is given to the quality-of-life and the management of emotions triggered by their social condition. Objective: To analyze the social and social security profile of patients undergoing radiotherapy treatment at Hospital de Base de São José do Rio Preto and to correlate them with their quality-of-life. Method: Descriptive exploratory study, with a quantitative approach, with 60 patients diagnosed with cancer in radiotherapy. Two evaluation questionnaires, one socioeconomic and social security of Graciano & Lehfeld and the Whoqol-bref, generic of quality-of-life. Results: During treatment there was a negative effect on quality-of-life, in the physical and psychological domains, impacting the positive correlations between education versus quality-of-life and retirement versus quality-of-life, revealing that social and social security issues have considerable influence on these specificities. Conclusion: The importance of the communicative behavior of the multidisciplinary team, through well-coming, qualified and humanized listening, and a comprehensive consultation evaluating the quality-of-life can minimize the factors affecting daily life and encourage them to proper adherence to treatment.